Magnetic resonance imaging findings among young adults with low back pain at Nsambya hospital - Komakech Richard Lukecha; Erem Geoffrey; Mubuuke A. Gonzaga; Bugeza Sam (BMC Medical Imaging, 2022)
Abstract Background Studies on MRI findings among patients with LBP have been conducted; especially among adolescents and young adult population in developed countries. However, MRI lumbar spine evaluation findings in young adult patients with low back pain in Uganda is not known. The purpose of this study was to determine the MRI findings and their correlation to clinical features in young adult patients with low back pain in Nsambya hospital. Methods This was a descriptive cross sectional study. One hundred and fifty-seven patients with low back pain in the 18–39 year age group underwent MRI lumbar spine evaluation. The MRI changes in the lumbar spine and correlation to clinical features were determined. Correlation was assessed by Pearson chi square tests (Fisher’s exact test) and p values reported at 0.05 level of significance. Results Of the 157 patients 129 (82.2%) had severe pain, whereas ninety (57.3%) had pain that had lasted more than 10 weeks. Sixty-five (41.4%) patients were found to have MRI evidence of disc desiccation, majority (61%) of whom had multiple level disease, mostly involving the lowest 2 disc levels. Facet joint arthropathy (47.8%), marginal osteophyte (31.8%) and disc contour irregularity [disc bulge] (31.2%) were other common MRI features seen. There was an association between duration of pain and limb weakness, and development of marginal osteophytes. There was also association between clinical presentation and disc bulge. Conclusions The MRI finding of disc degeneration among young adult patients with LBP is higher than reported. Age and pain distribution are predictors of developing disc desiccation.